Evaluation of 20 KV Distribution System Using SAIDI and SAIFI Reliability Indices at PT PLN - Linda Sartika; Al Amin Hanifa Muslim; Prasetia, Abdul Muis (Emitor: Jurnal Teknik Elektro, 2024)
Currently, power outages in Tarakan City are still frequent, both planned and due to disturbances such as fallen trees, lightning strikes or damage to the distribution equipment itself. PT PLN (Persero) Tarakan continues to make improvements to improve the reliability of the distribution system in Tarakan City using standard values, the reliability index for duration of disturbance (SAIDI) and the number of blackouts (SAIFI) so that the distribution of electrical energy continues to be channeled to customers. SAIDI and SAIFI values will be calculated every month to find out corrective actions against disturbances or damage that occur. Reliability is a benchmark value to see the reliability of the distribution system. The reliability index of SAIDI and SAIFI of PT. PLN (Persero) Tarakan in 2020 was 2.81 hours/plg/month and 2.55 times/plg/month. In 2021, SAIDI and SAIFI received 1.72 hours/plg/month and 2.45 times/plg/month. Based on the reliability index, PT PLN (Persero) Tarakan is categorized as reliable because the SAIDI and SAIFI values obtained do not exceed the existing standard values based on SPLN 68-2: 1986